2008
DOI: 10.2174/138920208786241234
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Vertebrate Toll-Like Receptors During Evolution

Abstract: Human toll-like receptors (TLRs) recognize pathogen-associated molecular patterns (PAMPs) to raise innate immune responses. The human TLR family was discovered because of its sequence similarity to fruit fly (Drosophila) Toll, which is involved in an anti-fungal response. In this review, we focus on the origin of the vertebrate TLR family highlighted through functional and phylogenetic analyses of TLRs in non-mammalian vertebrates. Recent extensive genome projects revealed that teleosts contain almost all subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 41 publications
(52 reference statements)
1
44
0
1
Order By: Relevance
“…Both, TLR3 and TLR22 serve as a dsRNA recognition receptor and recruit a common adaptor, TICAM-1. But, as shown by the phylogenetic analysis, TLR22 does not belong to the TLR3 family [16,21,40]. Why are there two TLRs that respond to dsRNA in teleosts?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both, TLR3 and TLR22 serve as a dsRNA recognition receptor and recruit a common adaptor, TICAM-1. But, as shown by the phylogenetic analysis, TLR22 does not belong to the TLR3 family [16,21,40]. Why are there two TLRs that respond to dsRNA in teleosts?…”
Section: Discussionmentioning
confidence: 99%
“…200 AE 20 embryos of each group were sample at 0, 8,16,24,32,40,48,56, and 64 h post-fertilization, the expression profile of CiTLR22 and CiTLR3 mRNA in embryos was assessed using RT-PCR as described above and real-time quantitative reverse transcription PCR (qRT-PCR) as described in the following section. The relative expression ratio of the target gene versus the b-actin gene were calculated using the 6CT method.…”
Section: Expression Profiles Of Citlr22 and Citlr3 In Tissue And Durimentioning
confidence: 99%
“…This finding is the first description of TLR agonist-stimulated responses in tuatara, and suggests that, like those of most other multicellular organisms, tuatara immune cells express TLR homologues for TLR2, TLR3, TLR4 and TLR 7/8. Functional studies have shown that vertebrate orthologues of TLR have the same function and recognition as their human counterpart; for example, Takifugu rubripes (Japanese pufferfish) TLR3, like human TLR3 responds to poly I:C (Oshiumi et al 2008). Furthermore, this idea is supported by DNA sequence comparisons of TLR genes in reptiles, birds, Drosophila, and mammals, revealing genes that have remained highly conserved throughout vertebrate evolution (Kimbrell & Beutler 2001;Armant & Fenton 2002;Roach et al 2005).…”
Section: Tlr Agonists Induce Responses In Isolated Tuatara Leukocytesmentioning
confidence: 99%
“…Phylogenetic analyses showed that the vertebrate TLRs evolved independently by gene duplication prior to the divergence of protostomes and deuterostomes (Hughes and Piontkivska, 2008;Roach et al, 2005). Gene loss and gene conversions were also suggested to have occurred (Huang et al, 2011;Kruithof et al, 2007;Oshiumi et al, 2008;Rebl et al, 2010;Temperley et al, 2008). Although vertebrate TLRs have been cited as an example of evolutionary conservation and strong functional constraint (Roach et al, 2005), recent studies suggested positive selection in some TLRs in extremely broad organisms including primates fishes or birds (Chen et al, 2008;Huang et al, 2011;Jann et al, 2008;Nakajima et al, 2008;Park et al, 2010;Tschirren et al, 2011;Wlasiuk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%